2017
DOI: 10.25019/mdke/5.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring CSR Strategy to Company Size?

Abstract: Abstract. Corporate Social Responsibility (CSR) is one of the most debated topics in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 73 publications
0
25
2
2
Order By: Relevance
“…Pressure from top management and stakeholder is considered as major influence in businesses going green. Both Zbuchea and Pinzaru's () and Sarvaiya, Eweje, and Arrowsmith's () research showed that strong commitment from managers would increase sustainability strategies and implementation. Hamann, Smith, Tashman, and Marshall's () survey of 55 South African wine firms also showed that managers' environmental responsibility is the key driver of their environmental behavior of SMEs.…”
Section: Drivers and Barriers To Smes' Sustainabilitymentioning
confidence: 98%
“…Pressure from top management and stakeholder is considered as major influence in businesses going green. Both Zbuchea and Pinzaru's () and Sarvaiya, Eweje, and Arrowsmith's () research showed that strong commitment from managers would increase sustainability strategies and implementation. Hamann, Smith, Tashman, and Marshall's () survey of 55 South African wine firms also showed that managers' environmental responsibility is the key driver of their environmental behavior of SMEs.…”
Section: Drivers and Barriers To Smes' Sustainabilitymentioning
confidence: 98%
“…In recent years, organisations recognised their social responsibility with more clarity and started considering it to be a part of their identity (Commission of the European Communities, 2001). Seeing that CSR can contribute to competitiveness (European Competitiveness Report, 2008), an increasing number of organisations are promoting socially responsible initiatives in response to the variety of environmental, social, and economic pressures ( Gazzola, 2017;Zbuchea and Pînzaru, 2017) and have CSR agendas (Hejjas et al, 2019).…”
Section: Corporate Social Responsibility From Stakeholder Management Perspectivementioning
confidence: 99%
“…With the exception of large companies, none had implemented/certified an environmental management system. This result was expectable because usually micro and small companies have neither the personnel nor financial resources for such activity, and CSR is dedicated mainly to large corporations [54]. On the other hand, all of them communicated with stakeholders about environmental issues.…”
Section: Hypothesismentioning
confidence: 99%
“…The hypothesis comes from the general opinion that CSR is useful mostly in cases of large budgets and, therefore, it is dedicated to large enterprises [54].…”
Section: The Corporate Social Responsibility Of Companies Producing Paraffin Waxesmentioning
confidence: 99%